Modeling sacsin depletion in Danio Rerio offers new insight on retinal defects in ARSACS - Valentina Naef; Devid Damiani; Rosario Licitra; Maria Marchese; Stefania Della Vecchia; Matteo Baggiani; Letizia Brogi; Daniele Galatolo; Silvia Landi; Filippo Maria Santorelli (Neurobiology of Disease)
Biallelic mutations in the SACS gene, encoding sacsin, cause early-onset autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS), a neurodegenerative disease also characterized by unique and poorly understood retinal abnormalities. While two murine models replicate the phenotypic and neuronal features observed in patients, no retinal phenotype has been described so far. In a zebrafish knock-out strain that faithfully mirrors the main aspects of ARSACS, we observed impaired visual function due to photoreceptor degeneration, likely caused by cell cycle defects in progenitor cells. RNA-seq analysis in embryos revealed dysfunction in proteins related to fat-soluble vitamins (e.g., TTPA, RDH5, VKORC) and suggested a key role of neuroinflammation in driving the retinal defects. Our findings indicate that studying retinal pathology in ARSACS could be crucial for understanding the impact of sacsin depletion and may offer insights into halting disease progression.